Solid phase synthesis of 5'-diphosphorylated oligoribonucleotides and their conversion to capped m7Gppp-oligoribonucleotides for use as primers for influenza A virus RNA polymerase in vitro. - Brownlee, G; Fodor, E; Pritlove, D; Gould, K; Dalluge, J (1995)
We have synthesized four different 5'-diphosphorylated oligoribonucleotides, varying in length from 11 to 13 nucleotides by a new solid phase method. After deprotection and partial purification the 5'-diphosphorylated oligoribonucleotides could be converted to capped (m7Gppp) oligoribonucleotides using guanylyl transferase. Radiolabelled capped oligoribonucleotides acted as primers for the influenza A virus RNA polymerase in vitro. The solid phase method described here should also allow the addition of 5'-diphosphates to synthetic oligodeoxyribonucleotides and be capable automation.